Combined computational and experimental investigation of high temperature thermodynamics and structure of cubic ZrO2 and HfO2. Issue 1 (December 2018) - Hong, Qi-Jun; Ushakov, Sergey; Kapush, Denys; Benmore, Chris; Weber, Richard; van de Walle, Axel; Navrotsky, Alexandra
Abstract Structure and thermodynamics of pure cubic ZrO2 and HfO2 were studied computationally and experimentally from their tetragonal to cubic transition temperatures (2311 and 2530 °C) to their melting points (2710 and 2800 °C). Computations were performed using automatedab initio molecular dynamics techniques. High temperature synchrotron X-ray diffraction on laser heated aerodynamically levitated samples provided experimental data on volume change during tetragonal-to-cubic phase transformation (0.55 ± 0.09% for ZrO2 and 0.87 ± 0.08% for HfO2 ), density and thermal expansion. Fusion enthalpies were measured using drop and catch calorimetry on laser heated levitated samples as 55 ± 7 kJ/mol for ZrO2 and 61 ± 10 kJ/mol for HfO2, compared with 54 ± 2 and 52 ± 2 kJ/mol from computation. Volumetric thermal expansion for cubic ZrO2 and HfO2 are similar and reach (4 ± 1)·10−5 /K from experiment and (5 ± 1)·10−5 /K from computation. An agreement with experiment renders confidence in values obtained exclusively from computation: namely heat capacity of cubic HfO2 and ZrO2, volume change on melting, and thermal expansion of the liquid to 3127 °C. Computed oxygen diffusion coefficients indicate that above 2400 °C pure ZrO2 is an excellent oxygen conductor, perhaps even better than YSZ.